A acessibilidade às informações sobre os processos de licenciamento ambiental no Brasil: análise dos websites dos órgãos ambientais licenciadores estaduais - Lima, Rafaela Silva de Oliveira de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The Access to Information Law nº 12.527/2011, has publicity as its general principle, and data confidentiality becomes an exception, thus ensuring that non-confidential information produced by the Public Power must be made available to citizens. Considering the protection of this right, this research aimed to analyze the situation of environmental agencies responsible for environmental licensing in all Brazilian states and the Federal District, with regard to the availability of information on environmental licensing processes on their websites. To this end, the availability of the following documents present in the environmental licensing processes on the websites of Organs licensing bodies was verified: Terms of Reference (TRs), Environmental Impact Studies (EIAs) and Environmental Impact Reports (RIMAs), Minutes of public hearings and environmental licenses issued. As a result, all states follow federal legislation nº 12.527/11, but in relation to the availability of documents, no environmental agency has fully presented all the documents analyzed, however, in the states of Rio de Janeiro, Espírito Santo, Mato Grosso, Distrito Federal, Rondônia and Bahia, the publicity of information by the licensing agencies was considered satisfactory, due to the presence of most documents, which did not occur in the other states. In view of the above, due to the absence of documents and the lack of systematization of information, which makes it difficult to access the documents of the environmental licensing processes, it is identified that environmental licensing agencies need adjustments in their websites to effectively guarantee the right of access to information.

A Lei de Acesso à Informação nº 12.527/2011, tem como princípio geral a publicidade, e o sigilo de dados se torna uma exceção, assegurando assim que informações não sigilosas produzidas pelo Poder Público devem ser disponibilizadas aos cidadãos. Considerando a proteção deste direito, esta pesquisa teve como objetivo analisar a situação dos órgãos ambientais responsáveis pelo licenciamento ambiental em todos os estados brasileiros e o Distrito Federal, no que se refere à disponibilização de informações sobre os processos de licenciamento ambiental em seus websites. Para tal, se averiguou a disponibilidade dos seguintes documentos presentes nos processos de licenciamento ambiental nos websites dos órgãos licenciadores: Termos de Referência (TRs), Estudos de impactos ambientais (EIAs), Relatórios de impactos ambientais (RIMAs), Atas de audiências públicas e licenças ambientais emitidas. Como resultado, todos os estados seguem a legislação federal nº 12.527/11, mas em relação a disponibilidade de documentos, nenhum órgão ambiental apresentou de forma integral todos os documentos analisados, no entanto, nos estados do Rio de Janeiro, Espírito Santo, Mato Grosso, Bahia, Rondônia e no Distrito Federal, a publicidade de informações por parte dos órgãos licenciadores foi considerada satisfatória, devido a presença da maioria dos documentos, o que não ocorreu nos demais estados. Diante do exposto, em razão da ausência de documentos e a falta de sistematização das informações, que dificulta o acesso os documentos dos processos de licenciamento ambiental, identifica-se que os órgãos licenciadores ambientais necessitam de adequações em seus websites para a efetiva garantia do direito de acesso às informações.
Accessibility to information about the processes of environmental licensing in Brazil: websites analysis state licensing environmental bodies
Keywords: Right to information; Social participation; Environmental citizenship; Direito à informação; Participação social; Cidadania ambiental